Multiobjective evolutionary algorithms NSGA-II and NSGA-III for software product lines testing optimization - Jamil, Muhammad Abid; Alhindi, Ahmad; Arif, Muhammad; Nour, Mohamed K; Awang Abu Bakar, Normi Sham; Aljabri, Tareq Fahad (Institute of Electrical and Electronics Engineers Inc., 2020)
Software Product line (SPL) engineering methodology utilizes reusable components to generate a new system for a specific domain. In fact, the product line establishes requirements, reusable components, architecture, and shared products to develop new products’ functionalities. In order to maintain high quality, there is a need for a thorough testing process. Each product in SPL having a different number of features need to be tested. Hence, the testing process of SPL can utilize a multi-objective optimization algorithm to optimize the testing process. This research, reports on the performance of a multi-objective Evolutionary Algorithms Non-Dominated Sorting Genetic Algorithm II (NSGA-II) and NSGA-III on Feature Models (FMs) to optimize SPL testing.